Generation of primary tumors with Flp recombinase in FRT-flanked p53 mice - Chang-Lung Lee; Everett J. Moding; Xiaofang Huang; Yifan Li; Loretta Z. Woodlief; Rafaela C. Rodrigues; Yan Ma; David G. Kirsch (The Company of Biologists, 2012)
SUMMARY The site-specific recombinases Cre and Flp can mutate genes in a spatially and temporally restricted manner in mice. Conditional recombination of the tumor suppressor gene p53 using the Cre-loxP system has led to the development of multiple genetically engineered mouse models of human cancer. However, the use of Cre recombinase to initiate tumors in mouse models limits the utilization of Cre to genetically modify other genes in tumor stromal cells in these models. To overcome this limitation, we inserted FRT (flippase recognition target) sites flanking exons 2-6 of the endogenous p53 gene in mice to generate a p53FRT allele that can be deleted by Flp recombinase. We show that FlpO-mediated deletion of p53 in mouse embryonic fibroblasts impairs the p53-dependent response to genotoxic stress in vitro. In addition, using FSF-KrasG12D/+; p53FRT/FRT mice, we demonstrate that an adenovirus expressing FlpO recombinase can initiate primary lung cancers and sarcomas in mice. p53FRT mice will enable dual recombinase technology to study cancer biology because Cre is available to modify genes specifically in stromal cells to investigate their role in tumor development, progression and response to therapy.